Ferromagnetism,variable range hopping,and the anomalous Hall effect in epitaxial Co：ZnO thin film - 白洪亮 贺树敏 徐同帅 刘国磊 颜世申 朱大鹏 代正坤 杨丰帆 代由勇 陈延学 梅良模 (Chinese physics B, 2012)
A series of high quality single crystalline epitaxial Zn 0.95 Co 0.05 O thin films is prepared by molecular beam epitaxy.Superparamagnetism and ferromagnetism are observed when the donor density is manipulated in a range of 10 18 cm 3-10 20 cm 3 by changing the oxygen partial pressure during film growth.The conduction shows variable range hopping at low temperature and thermal activation conduction at high temperature.The ferromagnetism can be maintained up to room temperature.However,the anomalous Hall effect is observed only at low temperature and disappears above 160 K.This phenomenon can be attributed to the local ferromagnetism and the decreased optimal hopping distance at high temperatures.